2022
DOI: 10.1017/s0144686x22000642
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review exploring the ‘grey area’ of suicide-related expression in later life: Developing a conceptual framework for professional engagement

Abstract: As the body of research on suicide in later life has developed, so has its vocabulary. This has generated a high level of overlap in concepts and terminology used to articulate suicide and how it might present, as well as ‘grey area’ behavioural terms that are both specific to older adults and less well-defined (e.g. ‘hastening of death’ or ‘completed life’). A better understanding of individual experiences and pathways to suicide can help to inform assessment and interventions, and increase the potential to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…Participants in our study demonstrated a greater awareness of their own end of life, associated with later life and possibly with a reduced fear of death or wish to die made more explicit in relation to their loss and potential losses. A scoping review of suicide and suicide-related concepts in older people [ 21 ] included a range of “grey area” behaviours (for lack of a better term) that are either less common, or present differently than they are in younger population groups. These include terms and behaviours such as “completed life”, “hastening of death” and “self-chosen death” [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in our study demonstrated a greater awareness of their own end of life, associated with later life and possibly with a reduced fear of death or wish to die made more explicit in relation to their loss and potential losses. A scoping review of suicide and suicide-related concepts in older people [ 21 ] included a range of “grey area” behaviours (for lack of a better term) that are either less common, or present differently than they are in younger population groups. These include terms and behaviours such as “completed life”, “hastening of death” and “self-chosen death” [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There may be a need to unify research from different disciplines, with policy themes on ageing such as healthy ageing, concepts of promoting person-centredness within service provision and giving greater emphasis to participation which enables peer support. Being able to understand the individual experiences and pathways within suicide research can help inform and enrich assessment and evidence-based interventions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One key message is that recognizing triggers that cause older people to “give up” on life can be difficult (Azulai and Walsh, 2015 ; Hafford-Letchfield et al, 2020 ). A recent conceptual model described several (so-called “gray area”) suicidal behaviors that might be considered unique to suicide expression in later life (Hafford-Letchfield et al, 2022a ). Yet, these expressions are viewed by many as “normal” part of aging, with such behaviors often described as a “rational” response to an age-related decline in physical or mental function (De Leo, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, these expressions are viewed by many as “normal” part of aging, with such behaviors often described as a “rational” response to an age-related decline in physical or mental function (De Leo, 2022 ). The conceptual model presented by Hafford-Letchfield et al ( 2022a ) described how an older adult viewing their life as “completed” could lead to the development of a wish to die and subsequently motivate engagement with a range of behaviors that either are self-destructive (e.g., self-neglect and problematic substance use) or hasten death (e.g., voluntary stopping of eating or drinking and refusing necessary medication).…”
Section: Introductionmentioning
confidence: 99%